Cash Holdings and Firm Performance in the Restaurant Industry - Kim, Jung Hoon; Lim, Jaeseong; Ahn, Jin Sun; Kim, Youngbin (Journal of Applied Business and Economics, 2023)
This study explores the link between cash holdings and performance outcomes in public restaurant companies in the United States, leveraging the critical role played by the industry context. We hypothesize that cash holdings have positive associations with both short-term and long-term firm performance in the restaurant industry. Our empirical analyses, based on fixed-effect regression models that control for all time-invariant variables, reveal that holding cash can improve performance in the restaurant industry, in support of our hypotheses.
Number: 3
Keywords: dept.mgt; firm performance; peer-reviewed

The Crisis of Danbury Fair Mall - Ahn, Jin Sun; Chung, Hanyong; Kim, Jung Hoon; Kim, Youngbin; Shin, Natalie Jungyoun (Journal of Marketing Development and Competitiveness, 2021)
This case describes the difficult financial situation of Danbury Fair Mall, which is the second biggest shopping mall in Connecticut. After World War II, the shopping mall business had grown fast especially in suburban areas of the U.S. However, the increasing popularity of online shopping caused extensive damage to shopping malls. This case will provide students the chance to think about the past, the present, and the future of the shopping mall industry in the U.S
Number: 2
Keywords: Connecticut; dept.acc; dept.mgt; peer-reviewed; ⛔ No DOI found